Correction of the Exon 2 Duplication in DMD Myoblasts by a Single CRISPR/Cas9 System - Lattanzi, Annalisa; Duguez, Stephanie; Moiani, Arianna; Izmiryan, Araksya; Barbon, Elena; Martin, Samia; Mamchaoui, Kamel; Mouly, Vincent; Bernardi, Francesco; Mavilio, Fulvio; Bovolenta, Matteo (Molecular therapy. Nucleic acids, 2017)
Exonic duplications account for 10%–15% of all mutations in Duchenne muscular dystrophy (DMD), a severe hereditary neuromuscular disorder. We report a CRISPR (clustered regularly interspaced short palindromic repeat)/Cas9-based strategy to correct the most frequent (exon 2) duplication in the DMD gene by targeted deletion, and tested the efficacy of such an approach in patient-derived myogenic cells. We demonstrate restoration of wild-type dystrophin expression at transcriptional and protein level in myotubes derived from genome-edited myoblasts in the absence of selection. Removal of the duplicated exon was achieved by the use of only one guide RNA (gRNA) directed against an intronic duplicated region, thereby increasing editing efficiency and reducing the risk of off-target effects. This study opens a novel therapeutic perspective for patients carrying disease-causing duplications. [Display omitted]